Theoretical study on YH6 cubic system based on ab initio methods - Begagra, Anfal; Khenchoul, Salah (Université Amar Telidji - Laghouat - Département des sciences de la matière, 2022)
The objective of this work is calculation of the structural, andVibrational properties in addition to critical temperature, superconducting gap, and coherence length of cooper pairs of YH, which is one of the new superconductors called Clathrate Yttrium hydride which has cubic structure that appears at high pressures. The calculation was conducted using ABINIT code in the framework of the functional theory of density (DFT), and the density functional perturbation theory (DFPT), It is characterized by high temperature at high pressure and this is what we have observed in the results obtained, although our results seem to be somewhat distant from the available data, we are not out of the general trend frame of this type of superconductors.